Be true to me - Griffin, Adele (Algonquin, 2017)
Told in two voices, Jean, a rich girl, and Fritz, an outsider, compete for the affection of handsome newcomer Gil during the summer of 1976 at an exclusive Fire Island enclave, and discover their competition has higher stakes than either can imagine.